Specific Issues on the Design and Expertise of Steel Columns for Overhead Lines. (2016) - Iuhos, Vincentiu Cristian; Campian, Cristina Mihaela
Abstract: The article presents a study on the design and expertise of steel columns for overhead power lines for high voltage transportation. In our days is a matter of safety to verify and maybe redesign some component elements. The collapse of the columns in actual changing climate conditions can be eliminated by developing methods of structural upgrading, which has to be efficient from the implementation technology point of view, as well as costs.